9g-2g-5g=16

Simple and best practice solution for 9g-2g-5g=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9g-2g-5g=16 equation:


Simplifying
9g + -2g + -5g = 16

Combine like terms: 9g + -2g = 7g
7g + -5g = 16

Combine like terms: 7g + -5g = 2g
2g = 16

Solving
2g = 16

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '2'.
g = 8

Simplifying
g = 8

See similar equations:

| 11+8x+19=20x+6 | | 0.03+0.08+0.7=0.2 | | 14t+-14t-t=18 | | W-22=31 | | X^4-4x^3+16x-16= | | 2x+3-5+2=4x*5 | | 4n+4+5=8 | | -2p-3(3-3p)=4(p-2)-22 | | 15*15=X^2+x^2 | | 3u+16=40 | | 3cosx+4sinx+7=0 | | (9x-8)+8= | | 42*42=(20.4*20.4)+x^2 | | 2x-6+x=42 | | (5x+7)+(-2x+2)= | | a-6=16+6a | | (3x-5)+y=27 | | 12/8=x | | 3j^2-30j+12=0 | | (2x+10)+7= | | (4x+4)+(-2x-2)= | | 2*3x-5=x+13 | | -3x+2=3(3x) | | 3y+19=6(9+y)+14 | | 4(8x-7)+15x= | | -1.8+0.4a=0 | | -3x-5(-2x+8)=-5 | | 6y+13=15 | | -18z-0.7=-28z+1.5 | | -1.8+0.4a=5 | | -3(2a-3b)= | | 7x+-8=6 |

Equations solver categories